The Gender Line Men, Women, and the Law - Levit, Nancy (Critical America, 1998)
Despite tremendous advances in civil rights, we live in a world where the sexes remain sharply segregated from birth to death: in names, clothing, social groupings, and possessions; in occupations, civic association, and domestic roles. Gender separatism, so pervasive as to be almost invisible, permeates the fabric of our daily social routines. Preferring a notion of gender that is fluid and contextual, and denying that separatism is inevitable, Nancy Levit dismantles the myths of gender essentialism Drawing on a wealth of interdisciplinary data regarding the biological and cultural origins of sex differences, Levit provides a fresh perspective on gendered behaviors and argues the need for careful cultivation of new relations between the sexes. With its focus particularly on men, The Gender Line offers an insightful overview of the construction of gender and the damaging effects of its stereotypes. Levit analyzes the ways in which law legitimizes the social segregation of the sexes through legal decisions regarding custody, employment, education, sexual harassment, and criminal law. In so doing, she illustrates the ways in which men's and women's oppressions are intertwined and how law molds the very definition of masculinity. Applying feminist methodology to the doctrine of feminism itself, Levit artfully demonstrates that gender separatism infects even our contemporary views of feminism. Levit asks questions that have been too long been unspoken--those that lie at the core of the feminist project, yet threaten its very foundations. Revealing masculinity as both a privileged and a victimized condition, she calls for a step forward, past the bounds of contemporary feminism and its conflicts, toward a more egalitarian and inclusive feminism. This brand of feminism would reshape traditional masculinity, invite men into feminist dialogue, and claim men as political allies.